A Broader Perspective on the Prenatal Diagnosis of Cornelia de Lange Syndrome: Review of the Literature and Case Presentation - Anca Maria Panaitescu; Simona Duta; Nicolae Gica; Radu Botezatu; Florina Nedelea; Gheorghe Peltecu; Alina Veduta (Diagnostics, 2021)
Cornelia de Lange syndrome (CDLS) is caused by pathogenic variants in genes which are structural or regulatory components of the cohesin complex. The classical Cornelia de Lange (CDLS) phenotype is characterized by distinctive facial features, growth retardation, upper limb reduction defects, hirsutism, and developmental delay. Non-classical phenotypes make this condition heterogeneous. Although CDLS is a heterogeneous clinical and genetic condition, clear diagnostic criteria have been described by specialist consensus. Many of these criteria refer to features that can be seen on prenatal ultrasound. The aim of this paper is twofold: to present the ultrasound findings in fetuses affected by CDLS syndrome; to discuss the recent advances and the limitations in the ultrasound and genetic prenatal diagnosis of CDLS. Our review aims to offer, apart from the data needed to understand the genetics and the prenatal presentation of the disease, a joint perspective of the two specialists involved in the prenatal management of this pathology: the fetal medicine specialist and the geneticist. To better illustrate the data presented, we also include a representative clinical case.